2016
DOI: 10.1089/ten.tec.2015.0439
|View full text |Cite
|
Sign up to set email alerts
|

Residual Detergent Detection Method for Nondestructive Cytocompatibility Evaluation of Decellularized Whole Lung Scaffolds

Abstract: The development of reliable tissue engineering methods using decellularized cadaveric or donor lungs could potentially provide a new source of lung tissue. The vast majority of current lung decellularization protocols are detergent based and incompletely removed residual detergents may have a deleterious impact on subsequent scaffold recellularization. Detergent removal and quality control measures that rigorously and reliably confirm removal, ideally utilizing nondestructive methods, are thus critical for gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 39 publications
4
52
0
Order By: Relevance
“…Moreover, SEM results showed that cells were attached and expanded efficiently after being in culture for 24 h. These results represent that high viability and less toxicity of decellularized scaffolds depend on various factors such as the percentage of applied detergent and an efficient washing process. These results are in accordance to those reported by Sullivan et al On the contrary, Zvarova et al have shown that an excessive washing step does not affect the viability and toxicity. In addition, Wang et al have shown that TX‐100 can expel the remained SDS of the tissue and reduces the toxicity; however, the results of this study are contrary to that reported by Wang.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, SEM results showed that cells were attached and expanded efficiently after being in culture for 24 h. These results represent that high viability and less toxicity of decellularized scaffolds depend on various factors such as the percentage of applied detergent and an efficient washing process. These results are in accordance to those reported by Sullivan et al On the contrary, Zvarova et al have shown that an excessive washing step does not affect the viability and toxicity. In addition, Wang et al have shown that TX‐100 can expel the remained SDS of the tissue and reduces the toxicity; however, the results of this study are contrary to that reported by Wang.…”
Section: Discussionsupporting
confidence: 93%
“…The decellularization solutions used in this study contain high concentrations of detergents that were chosen after an initial investigation that accounted for the time needed for decellularization. Residual detergents present after decellularization have been shown to affect cellular viability [41] and thus could become problematic with use of high detergent concentrations. There were at best only limited viability issues in this study, nevertheless, this and other potential concerns should be addressed with further refinement of the decellularization techniques.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies by our group and others have demonstrated feasibility of decellularized human, primate, pig and rat tissues in achieving some of these features (5, 18, 24, 29, 60-63). In this work, we demonstrated that the basement membrane (required to separate the blood supply), and the gross tissue architecture needed to provide gas exchange were maintained in each of our decellularized species.…”
Section: Discussionmentioning
confidence: 99%